Worker Trust in Management and Delegation in Organizations. (13th June 2020) - Meagher, Kieron J; Wait, Andrew
Abstract: Using a unique employee–establishment survey, we find a causal relationship between an individual employee's trust of management and their decision-making rights (delegation). We utilize both fixed effects (FE) and instrumental variables to control for unobserved factors: establishment-level FE control for management quality, practices, culture, and other characteristics; our instruments of inherited trust in management, and trust of equivalent workers in a different but similar country address the possible endogeneity of employee trust. Across all specifications, we find that delegation to a worker is more likely if that employee trusts management. In our preferred model, which includes establishment FE and accounts for endogeneity, we find a 1 standard deviation (SD) increase in employee trust increases delegation by approximately 0.6 of 1 SD. Our results are robust to the inclusion of worker preferences for individualism (which favors delegation), incentives/bonuses, and alternative measures of decision authority. ( JEL D23, L22, L23).